GE_GERICHTE P/8198/2023 vom 27. Januar 2025 - GE Cour de justice (2025)
CAPACITÉ D'ESTER EN JUSTICE;CURATELLE;DROITS STRICTEMENT PERSONNELS;ORDONNANCE PÉNALE;FORMALISME EXCESSIF;OPPOSITION(PROCÉDURE) | CPP.356; CPP.106; CC.390; CPP.127